Demonstration of electron beam excitation laser using a GaInN-based multiquantum well active layer. (31st August 2016) - Hayashi, Takafumi; Nagata, Noriaki; Senga, Takashi; Iwayama, Sho; Iwaya, Motoaki; Takeuchi, Tetsuya; Kamiyama, Satoshi; Akasaki, Isamu; Matsumoto, Takahiro
Abstract: In this study, an electron beam excitation laser using a GaInN-based multiquantum well (MQW) active layer was investigated, and laser emission was observed for the first time from a GaInN-based MQW excited by an electron beam. This technology has the potential to provide access to an expanded wavelength region for the laser action of nitride-semiconductor-based lasers from deep UV to infrared.